Contraceptives or Hormone Replacement Therapy and Associations with Autoimmune Conditions: Exploring Effects of Estrogen Analog Supplementation - Irakli Tskhakaia; Yurilu Gonzalez Moret; Anna‐Kay Palmer; Diego Lema; M. Carolina Musri; Nanuka Tsibadze; Arthur Lau (ACR Open Rheumatology)
Objective The aim of this study was to investigate the impact of estrogen and progesterone analog supplementation on the development of autoimmune conditions. Methods This retrospective observational study used data from the TriNetX network, which comprised over 100 million patients from 89 health care organizations. We compared patients exposed to estrogen and progesterone analogs to those exposed to progesterone‐only therapy, using 1:1 propensity score matching based on age, ethnicity, and additional criteria. The primary outcomes were incidences of various autoimmune conditions. Results We included 3,338,925 patients in the group who received estrogen and progesterone and 2,090,758 patients in the group who received progesterone only. Prematching, the group who received combined therapy showed increased risks for Sjögren disease (risk ratio [RR] 1.46), rheumatoid arthritis (RR 1.1), and other autoimmune conditions. Postmatching, significant associations persisted for most conditions, with increased risks for systemic sclerosis, systemic lupus erythematosus, giant cell arteritis, Behcet disease, psoriatic arthritis, reactive arthritis, and ankylosing spondylitis. The group who received combination therapy appeared to have lower risks of developing antiphospholipid syndrome (RR 0.7). Conclusion Combined estrogen and progesterone therapy is associated with an increased risk of several autoimmune conditions. The role of estrogen, despite its protective effects against some conditions, underscores the complex interplay of sex hormones in autoimmunity. Further prospective studies are needed to elucidate underlying mechanisms and evaluate causality.